La Depresión que presentan las estudiantes hijas de emigrantes del Cuarto al Séptimo año de Educación Básica de la Unidad Educativa “La Porciúncula” y su incidencia en el Rendimiento Académico, durante el periodo 2007-2008. Propuesta Alternativa - Carranza García, Edna Hercilia (2009)
The family is the fundamental pillar of the society; by as much when this one is disintegrated it affects to each one of its members; the emigration is one of the important causes by which it is disturbed, affecting in greater measurement the children, this causes that they present depression and they cannot render optimally in his studies. By before exposed and the important thing of the problematic one has been believed advisable to make a study on: “THE DREPRESIÓN THAT PRESENTS THE STUDENTS DAUGHTERS OF EMIGRANTS FROM THE QUARTER TO THE SEVENTH BASIC YEAR OF EDUCATION OF THE EDUCATIVE UNIT “LA PORCIÚNCULA” AND THEIR ACADEMIC YIELD, DURING PERIOD 2007-2008. ALTERNATIVE PROPOSAL”. To guide the present investigative work he/she thought about the following objectives: GENERAL: To contribute to improve the academic yield of the students daughters of emigrants from the room to seventh year of basic education of the Educational Unit "The Porciúncula" of the city of Loja through the knowledge and analysis of the problem. SPECIFIC: 1. To identify if the emigration of the family parents causes depression in the students. 2. To determine if the depression that the students present from the room to the seventh year of basic education, emigrants' of the Educational Unit daughters "The Porciúncula", it impacts in their academic yield, during the year lectivo 2007-2008. 3. To build an alternative proposal that allows to improve the academic yield of the students, emigrants' daughters from the room to seventh year of basic education of the Educational Unit "The Porciúncula". For that which a population of 183 people took among which 11 teachers, 86 representatives and 86 girls consist from the room to the seventh year of basic education of the Educational Unit "The Porciúncula" to who were applied technical instruments as: the Test of Yesavage (abbreviated version) and the Surveys to determine the depression level, the emigration and the academic yield, with the obtained data of the application of these instruments were carried out the respective analysis and interpretation of the results. The results allowed to conclude that the emigration of the parents is the cause of the depression of the students and for ende the first floor academic yield. For it is recommended it to the parents to leave in hands of family reliable to their daughters and to be in continuous communication. Of this study you plates a denominated alternative proposal "Implementation of an informative shop for the teachers, representatives and students whose parents have emigrated from the Room to the Seventh year of Basic Education of the Educational Unit "The Porciúncula" whose general objective is to elaborate a so much training shop for the representatives like for the teachers about the depression and its incidence in the academic yield.